Uncovering the Mechanism of Thermally Activated Delayed Fluorescence in Coplanar Emitters Using Potential Energy Surface Analysis - Bergmann, Katrina; Hojo, Ryoga; Hudson, Zachary M. (The journal of physical chemistry letters, 2023)
Planarized emitters exhibiting thermally activated delayed fluorescence (TADF) have attracted attention due to their narrow emission spectra, improved photostability, and high quantum yields, but with large singlet–triplet energy gaps (ΔE ST ) and no heavy atoms, the origin of their TADF remains a subject of debate. Here we prepare two isomeric, coplanar donor–acceptor compounds, with HMAT-2PYM performing dual TADF and room-temperature phosphorescence but with HMAT-4PYM exhibiting only prompt fluorescence. Although conventional TADF design principles suggest that neither isomer should exhibit TADF, we reveal differences in the excited state potential energy surfaces that enable spin-flip processes in only one isomer. We also find that hydrogen bonding is absent between the planar units of these emitters, despite earlier claims of intramolecular hydrogen bonding in similar compounds. Overall, this work demonstrates that potential energy surface analysis is a practical strategy for designing coplanar TADF materials that might otherwise be overlooked by conventional TADF design metrics.